2022
DOI: 10.1002/cam4.5040
|View full text |Cite
|
Sign up to set email alerts
|

CT‐determined low skeletal muscle mass predicts worse overall survival of gastric cancer in patients with cachexia

Abstract: Background There were controversies for the association between computed tomography (CT)‐determined low skeletal muscle mass (SMM) and overall survival (OS) in gastric cancer (GC). In this study, we investigated whether cachexia could be a potential confounding variable for this issue. Methods We retrospectively collected the patients of GC in our institution between July 2016 and January 2021. Preoperative SMM was determined by analyzing the skeletal muscle index of L3 with abdominal CT, and the cut‐offs for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 34 publications
(80 reference statements)
0
7
0
Order By: Relevance
“…The original preoperative abdominal CT images of included patients were extracted from our hospital, and Syngo MultiModality Workplace (Siemens Medical Solutions, Forchheim, Germany) was used for analyzing the skeletal muscle area of the third lumbar vertebra (L3) level [ 24 ]. The Hounsfield unit (HU) threshold of skeletal muscle was set from −29 to 150 [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The original preoperative abdominal CT images of included patients were extracted from our hospital, and Syngo MultiModality Workplace (Siemens Medical Solutions, Forchheim, Germany) was used for analyzing the skeletal muscle area of the third lumbar vertebra (L3) level [ 24 ]. The Hounsfield unit (HU) threshold of skeletal muscle was set from −29 to 150 [ 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, patients with low SMI were found to have a significantly higher rate of prolonged length of hospital stay. Many research and our study also has shown that the measurement of skeletal muscle composition using CT scans has a high predictive value for predicting postoperative complications and prognosis, and thus, this indicator is crucial for clinicians 11,25,50 . CT scans provide detailed information about skeletal muscle, which can be used to assess a patient's overall physical condition and muscle function.…”
Section: Discussionmentioning
confidence: 78%
“…Many research and our study also has shown that the measurement of skeletal muscle composition using CT scans has a high predictive value for predicting postoperative complications and prognosis, and thus, this indicator is crucial for clinicians. 11 , 25 , 50 CT scans provide detailed information about skeletal muscle, which can be used to assess a patient's overall physical condition and muscle function. Prior to surgery, CT scans can help identify the risk of low skeletal muscle mass in patients, enabling appropriate measures to be taken to reduce the occurrence of complications.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations